Agroecological business model diagnostics and upgrading plan for Sasso poultry business in Murehwa District, Zimbabwe - Matangi, Dorcas; Zingwena, Taurai; Debello, Jaleta Moti; Ngoma, Hambulo; Chimonyo, Vimbayi G. P.; Dawes, M.; Mushongachiware, R. (CGIAR, 2024)
This report examines the development and upgrading of the Hamara Sasso poultry business model in Murehwa District, Zimbabwe, as part of the CGIAR Agroecology Initiative. It synthesizes the processes followed to identify potential agroecological business models, diagnose their alignment with agroecological principles, and outline financial and viability assessments. The analysis includes findings from the Value Chain Analysis (VCA), Business Model Canvas, and agroecology assessments, along with a SWOT analysis and lessons learned from implementation challenges. Key results indicate that the Sasso model achieved a B-ACT agroecology score of 61.36%, reflecting partial alignment with agroecological principles such as inclusivity, resilience, and efficiency, while highlighting areas for improvement in resource recycling, market access, and cost-effective feed strategies. The SWOT analysis identified strengths such as high consumer demand for organic poultry, robust market potential, and the hardiness of the Sasso breed, contrasted with challenges like high feed costs, limited farmer access to financial and technical resources, and logistical inefficiencies. Recommendations focus on enhancing circularity through poultry manure recycling and promoting alternative feeds like Azolla to reduce production costs. Strengthening market linkages with urban retailers and institutional buyers, along with tailored financial products and cooperative models, will improve farmer profitability. Participatory training in feed formulation, disease management, and agroecological practices will increase farmer resilience, while investments in infrastructure, decentralized logistics, and digital platforms like the Hamara App will ensure scalability. Addressing these challenges positions the model as a scalable framework for agroecological and economic advancement in rural poultry systems.